Seizure Precipitants and Epilepsy Syndromes - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2001)
The prevalence of various seizure precipitants in relation to different epilepsy syndromes and patient age and gender was determined by a questionnaire survey of 400 patients attending (Dec 1998-May 1999) the Comprehensive Epilepsy Program, University of Virginia, Charlottesville.